Optimalisasi Harta Wakaf Sebagai Sarana Dakwah (Studi Kasus Yayasan At-Turots Al-Islamy Yogyakarta) - Sumarji, Musthofa; Ahsan, Khoirul (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Waqf has great potential to support social and da'wah activities in Indonesia, yet many waqf assets remain underutilized. This study aims to analyze the management practices of waqf assets, identify the level of optimization of waqf asset potential, and describe the system and strategies for optimizing waqf as a means of da'wah at the At-Turots Al-Islamy Foundation in Yogyakarta. This research employs a qualitative approach with a case study method. Data collection techniques include interviews, documentation, observation, and analysis of classical Islamic scholars' works. The findings reveal that the foundation manages waqf assets (land, buildings, vehicles, and cash waqf) based on Islamic sharia and the standards of the Indonesian Waqf Board (BWI), employing strategies such as activating idle assets, establishing an Islamic cooperative, and cooperating with third parties. Waqf fund collection is carried out through digital media, personal approaches, and fundraising events. The role of waqf in da'wah is proven to be significant, encompassing education, social welfare, productive economy, and creative da'wah programs. This study recommends the digitization of waqf management and the strengthening of productive waqf literacy.